Pulmonary vascular lesions in the toxic oil syndrome in Spain. Issue 10 (October 1983) - Fernández-Segoviano, P; Esteban, A; Martínez-Cabruja, R
Abstract : A histological study was made of pulmonary arteries at the necropsies of nine patients who died after the ingestion of denatured rapeseed oil during the epidemic which occurred in Spain in May 1981. Lesions found in the elastic pulmonary arteries were characterised by pronounced intimal proliferation of an oedematous nature, accumulation of large vacuolated cells within the media, and loss of vascular smooth muscle. In muscular pulmonary arteries there was pronounced medial hypertrophy and intimal proliferation, which was so severe in one case that it completely occluded the arterial lumen. Foamy cells were found in the intima. Muscularisation was seen in the walls of pulmonary arterioles.